The sociodrama of presidential politics : rethoric, ritual, and power in the era of teledemocracy. - McLeod, James R. (American Antropological Association, 1999)
In this paper I examine the American presidential campaign cycle as a series of ritualized sociodramas. Examples are used from the campaigns of 1988, 1992, and 1996 to illustrate the role of ritual, rhetoric, symbol, and media in the process of presidential power acquisition. These political processes are analyzed utilizing the concepts of sociodrama and rituals of rebellion extant in the literature of political anthropology. Specific cases such as the bus tours of the Clinton campaign, the Willie Horton commercials of the Bush campaign, and the case of Murphy Brown are examined in detail. The goal of the paper is to render an anthropological perspective on the process of choosing the American President in the era of teledemocracy.